Osteogenic effect of bone marrow mesenchymal stem cell-derived exosomes on steroid-induced osteonecrosis of the femoral head - Fang S; Li Y; Chen P (Dove Medical Press, 2018)
Shanhong Fang,1,* Yongfeng Li,2,* Peng Chen1 1Department of Orthopedic Surgery, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350005, China; 2Department of Bone Surgery, Fujian Medical University, Fuzhou 350005, China *These authors contributed equally to this work Background: Animal studies have demonstrated the therapeutic effect of mesenchymal stem cells (MSCs) on osteogenesis, but little is known about the functions of exosomes (Exos) released by bone MSCs (BMSCs). Here, we investigated the effect of BMSC Exos on steroid-induced femoral head necrosis (SFHN) and explored the vital genes involved in this process. Materials and methods: BMSCs were isolated from healthy and SFHN rats. BMSC Exos were isolated using the Exosome Precipitation Kit and characterized by transmission electron microscopy and Western blotting. SFHN BMSCs were incubated with Exos from healthy BMSCs. Osteogenic ability was assessed by oil red O staining and alizarine red staining. Differentially expressed genes (DEGs) induced by Exos were screened using the Osteogenesis RT2 Profiler PCR Array. The effect of upregulated Sox9 was examined using lentivirus-mediated siRNA. Results: The results revealed that BMSC Exos were 100–150 nm in size and expressed CD63. Moreover, BMSC Exo-treated SFHN cells exhibited suppressed adipogenesis compared to model cells. PCR array showed that eleven and nine genes were upregulated and downregulated, respectively, in the BMSC Exo-treated SFHN cells compared to the model group. Among the DEGs, osteogenesis-related genes, including Bmp2, Bmp6, Bmpr1b, Mmp9, and Sox9, may play important roles in SFHN. Furthermore, the DEGs were mainly involved in immune response, osteoblast differentiation, and in the transforming growth factor-β/bone morphogenetic protein signaling pathway. The level of the SOX9 protein was upregulated by Exos, and Sox9 silencing significantly decreased the osteogenic effect of BMSC Exos. Conclusion: Our data suggest that Exos derived from BMSCs mainly affect SFHN osteogenesis, and this finding can be further investigated to develop a novel therapeutic agent for SFHN. Keywords: exosome, bone marrow mesenchymal stem cells, steroid-induced femoral head necrosis, gene expression, ostosis